THE EFFECTIVENESS OF STUDENT TEAMS ACHIEVEMENT DIVISION TO TEACH WRITING VIEWED FROM STUDENTS’ CREATIVITY - Rahmatika, Annisa (International Journal of Language Education, 2019)
Student Teams Acievement Division (STAD) is one of the simplest of all cooperative learning methods, where team works in learning English provides students with the team opportunity to express and to communicate with each other. One of the ways to make them express and communicate with each other is by dividing the class into several team works or groups. This experimental study sought to find out the effectiveness of STAD to teach writing viewed from students’ creativity in the tenth grade of SMAN 1 JATIWARAS Tasikmalaya in the academic year of 2017/2018. Recruitment strategy was through cluster random sampling resulting 2 classes which consist of 28 students of each class contributed to the study. Data collection technique encompassed creativity test and writing test. The data were analyzed thoroughly by using 2x2 Multifactor Analysis of Variance (ANOVA) and Tukey’s HSD Test. The result revealed that: (1) Student Teams Acievement Division (STAD) is more effective than Direct Method to teach writing; (2) students having high creativity have better writing skill than those having low creativity. (3) there is an interaction between teaching methods and students’ creativity. Keywords: STAD, Direct Method, writing skill, students’ creativity.